2008
DOI: 10.1123/jpah.5.s1.s98
|View full text |Cite
|
Sign up to set email alerts
|

Use of Accelerometers in a Large Field-Based Study of Children: Protocols, Design Issues, and Effects on Precision

Abstract: Background:Objective methods can improve accuracy of physical activity measurement in field studies but uncertainties remain about their use. Methods: Children age 11 years from the Avon Longitudinal Study of Parents and Children (ALSPAC), were asked to wear a uni-axial accelerometer (MTI Actigraph) for 7 days. Results: Of 7159 children who attended for assessment, 5595 (78%) provided valid measures. The reliability coefficient for 3 days of recording was .7 and the power to detect a difference of 0.07 SDs (P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
347
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 341 publications
(359 citation statements)
references
References 18 publications
9
347
3
Order By: Relevance
“…The sample (n=17,663, aged 16-92 years at baseline) included participants of two studies aimed at assessing and preventing CVD: the National Research Program 1A (NRP 1A) (Gutzwiller et al, 1985), and the Swiss MONICA (MONItoring of trends and determinants in CArdiovascular disease) study (Mattocks et al, 2008). The NRP 1A was conducted from 1977-79 in the three main language regions of Switzerland based on a random sample of 4378 and a convenience sample of 3873 participants (Bopp et al, 2012).…”
Section: Study Populationmentioning
confidence: 99%
“…The sample (n=17,663, aged 16-92 years at baseline) included participants of two studies aimed at assessing and preventing CVD: the National Research Program 1A (NRP 1A) (Gutzwiller et al, 1985), and the Swiss MONICA (MONItoring of trends and determinants in CArdiovascular disease) study (Mattocks et al, 2008). The NRP 1A was conducted from 1977-79 in the three main language regions of Switzerland based on a random sample of 4378 and a convenience sample of 3873 participants (Bopp et al, 2012).…”
Section: Study Populationmentioning
confidence: 99%
“…The details of accelerometer deployment in ALSPAC have been 225 previously described (Mattocks et al 2007;Mattocks et al 2008). All adolescents attending 226 research clinics at 15 years were asked to wear an Actigraph GT1M accelerometer (Actigraph 227 LLC, Fort Walton Beach, FL, USA) around their waist, over the right hip for seven 228 consecutive days.…”
Section: Participants 140mentioning
confidence: 99%
“…Practicalities of a "trial period" will of course depend on the study size and duration and number of participants. Previous studies have suggested that accelerometer measures tend to be higher on the first day of recording [22]. Some young people in the current study did report that it took them a little to get used to wearing the device.…”
Section: Discussionmentioning
confidence: 69%